Enhanced Survival in Mice Exposed to Ionizing Radiation by Combination of Gamma-Tocotrienol and Simvastatin. (21st March 2019) - Pathak, Rupak; Kumar, Vidya Prasanna; Hauer-Jensen, Martin; Ghosh, Sanchita Purohit
Abstract: Ionizing radiation exposure is a major concern for active military service members, as well as civilian population. Considering that the exposure is not predictable, it is imperative that strategies to counteract radiation damage must be discovered. Recent in vitro studies performed in our laboratory demonstrated that the vitamin E analog gamma-tocotrienol (GT3) in combination with cholesterol-lowering drugs (Statins), synergistically induced endothelial thrombomodulin, an anticoagulant with radio-protective efficacy. It was hypothesized that the combination of treatment with both GT3 along with Statins would provide better radiation protection in vivo than each drug individually. CD2F1 mice were injected subcutaneously with either vehicle or single dose of GT3 (200 mg/kg body weight) 24 hours before irradiation followed by oral or subcutaneous administration of various doses of simvastatin (25, 50, and 100 mg/kg body weight) before exposure to lethal doses (11.5 and 12 Gy) of Cobalt-60 ( 60 Co) gamma-irradiation. The combined treatment group exhibited enhanced radiation lethality protection substantially, accelerated white blood cell recovery, and augmented restoration of bone marrow cellularity when compared to the animals treated with either drug exclusively. This information clearly suggests that combined treatment could be used as a safeguard for military personnel from exposure to harmful ionizing radiation.